Manipulating Ion Concentration to Boost Two‐Electron Mn4+/Mn2+ Redox Kinetics through a Colloid Electrolyte for High‐Capacity Zinc Batteries. Issue 5 (26th December 2021) - Xie, Xuesong; Fu, Hongwei; Fang, Yun; Lu, Bingan; Zhou, Jiang; Liang, Shuquan
Abstract: Aqueous zinc batteries (ZBs) have flourished due to their advantages of low‐cost and intrinsically safe water‐based electrolytes. However, in the traditional liquid electrolyte, sufficient energy density and efficiency for practical utility have not been realized yet. Here, instead of the use of a strong acid/alkali pH environment to elevate the working voltage in an aqueous solution, an ion concentration/dilution strategy is proposed to trigger the extra deposition/dissolution capacity of the Mn 4+ /Mn 2+ redox reaction in normal Zn/MnO2 batteries. With the precipitation and release of Zn 2+ ions during the discharge/charge process, the adjustment of manganese concentration is successfully realized via the reciprocal Zn/Mn ionic exchange rendered by the bentonite colloidal (Ben‐colloid) electrolyte. This electrolyte also triggers a self‐dissolution/deposition reaction even in the cathode‐free system. Consequently, the Zn/MnO2 battery with Ben‐colloid electrolyte affords up to 1.7× capacity release (480.7 mAh g –1 ) on average compared with a liquid electrolyte at 0.2 A g –1, higher capacity retention (94.3% vs 63.6%) after 500 cycles at 1 A g –1, and good elevated‐temperature endurability (up to 80 °C). This work opens up a new horizon to improve the energy density of water‐based metal ion batteries by the use of a functional electrolyte. Abstract : A Mn ion concentration/dilution strategy enabled by inorganic Ben‐colloid electrolyte is proposed to reduce the equilibrium deposition potential and trigger the extra deposition/dissolution capacity of the Mn 4+ /Mn 2+ redox reaction in a Zn/MnO2 battery. The battery affords up to 1.7× capacity release compared with those using liquid electrolytes, higher capacity retention (94.3% vs 63.6%), and good elevated‐temperature resilience (up to 80 °C).